2017
DOI: 10.11152/mu-924
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation force impulse elastosonography of placenta in maternal red blood cell alloimmunization: a preliminary and descriptive study

Abstract: Aims: Maternal red blood cell alloimmunization is an important cause of fetal morbidity and mortality in the perinatal period, despite well-organized prophylaxis programs. The objective of the study was to evaluate placental elasticity by using Acoustic Radiation Force Impulse (ARFI) in Rhesus (Rh) alloimmunized pregnant women with hydropic and nonhydropic fetuses and to compare those with healthy pregnant women. Material and methods: This case-control and descriptive study comprised twenty-eight healthy pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[11][12][13] A limited number of human studies include healthy pregnancies, pregnancies with hypertensive disorders, and fetal abnormalities, investigating the elasticity of the placenta, fetal lungs, liver, brain, and myocardium. [14][15][16][17][18][19][20] As far as we know, our study is the first elastography research on both healthy pregnancies and pregnancies with chromosomal abnormalities including placenta, maternal myometrium, and tissues used in the genetic sonogram. Unfortunately, this study took place during the COVID-19 pandemic outbreak, where the referring number of patients was considerably decreased.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[11][12][13] A limited number of human studies include healthy pregnancies, pregnancies with hypertensive disorders, and fetal abnormalities, investigating the elasticity of the placenta, fetal lungs, liver, brain, and myocardium. [14][15][16][17][18][19][20] As far as we know, our study is the first elastography research on both healthy pregnancies and pregnancies with chromosomal abnormalities including placenta, maternal myometrium, and tissues used in the genetic sonogram. Unfortunately, this study took place during the COVID-19 pandemic outbreak, where the referring number of patients was considerably decreased.…”
Section: Discussionmentioning
confidence: 98%
“…In the literature, research is reported on the fetomaternal elastographic evaluation of dogs, sheep, and baboons 11–13 . A limited number of human studies include healthy pregnancies, pregnancies with hypertensive disorders, and fetal abnormalities, investigating the elasticity of the placenta, fetal lungs, liver, brain, and myocardium 14–20 . As far as we know, our study is the first elastography research on both healthy pregnancies and pregnancies with chromosomal abnormalities including placenta, maternal myometrium, and tissues used in the genetic sonogram.…”
Section: Discussionmentioning
confidence: 99%
“…SWE is a promising technique that is used to measure tissue stiffness in vivo. Placental stiffness in a healthy pregnancy or pregnancies accompanied by various pathologies has been studied in recent years (15,16,18,19). In the present study, the mean SWV was 1.69 AE 0.23 m/s in the control group, which was a higher value than the mean velocity values of previous studies, such as by Ohmaru et al (20) with a mean value of 0.98 AE 0.21 m/s, and by Wu et al (19) with a mean value of 0.98 AE 0.26 m/s in healthy pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Although stiffness was measured only from the maternal edge, studies have shown similar values in any region of the normal placenta indicating that SWE values from any region could be used for the overall stiffness of the placenta (24,25). Increased placental stiffness has been reported in many pathologies such as pre-eclampsia, Rh alloimmunized pregnant women with hydropic fetuses, or pregnancies with fetal anomalies, possibly due to some histopathological changes in the placenta (15,16,25). Sugitani et al (10) performed histopathological examinations on placentas showing increased SWV values and found widespread infarction and inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation